THE WAYS OF INCREASE OF THE ELECTROSLAG TECHNOLOGIES SAFETY AT PRODUCTION OF CASTINGS OF FERROUS AND NONFERROUS METALS - D. M. Kukuj; G. I. Kleshchenak; O. G. Tarnovskaja; E. G. Kleshchenak (Литьë и металлургия)
The ways of increase of the electroslag technologies safety at production of castings of ferrous and nonferrous metals are described.